Relationship Between Behavioral and Emotional Problems Using the Strengths and Difficulties Questionnaire (SDQ) and Academic and Sports Achievement Index Among Students at State Sports-Talented High School in Aceh - Mestika Kuine; Herlina Dimiati; T.M. Thaib; Rusdi Andid; Sulaiman Yusuf; Eka Yunita Amna (Journal of Health and Nutrition Research, 2026)
Adolescence represents a vulnerable developmental period characterized by rapid behavioral and emotional changes that significantly influence academic achievement and sports performance. The Strengths and Difficulties Questionnaire (SDQ) is a standardized screening instrument widely utilized to assess emotional symptoms, conduct problems, hyperactivity, peer relationship difficulties, and prosocial behavior in adolescents. This study aimed to investigate the relationship between behavioral and emotional problems measured by SDQ and academic and sports achievement indices among students at State Sports-Talented High School in Aceh. An observational analytical study with cross-sectional design was conducted involving 108 students aged 15-18 years. Data collection utilized SDQ self-report questionnaire, academic records, and sports achievement documentation. Statistical analysis employed Mann-Whitney test for academic achievement and Fisher's exact test for sports achievement with 95% confidence level. Total difficulties score demonstrated significant associations with academic achievement (p=0.035) and sports achievement (p=0.010). Emotional problems subscale showed significant correlations with both academic (p=0.007) and sports achievement (p=0.038). Conduct problems and peer relationship difficulties exhibited highly significant associations with sports achievement (p=0.001 and p<0.001 respectively). The findings indicated that 26.9% of participants reported abnormal total difficulties scores, suggesting a need for intervention. Behavioral and emotional problems significantly correlate with academic achievement and sports performance among talented sports students. These findings emphasize the importance of routine mental health screening using SDQ in sports-specialized schools to enable early identification and timely intervention